A GSH-activatable ruthenium(ii)-azo photosensitizer for two-photon photodynamic therapy. Issue 12 (25th January 2017) - Zeng, Leli; Kuang, Shi; Li, Guanying; Jin, Chengzhi; Ji, Liangnian; Chao, Hui
Abstract : The first dinuclear ruthenium(ii )-azo complex was developed as a glutathione (GSH)-activatable photosensitizer for use in two-photon photodynamic therapy upon irradiation in the NIR region. Abstract : A glutathione (GSH)-activatable ruthenium(ii )-azo photosensitizer was prepared. The complex had low toxicity towards cells under dark conditions. It exhibited excellent phototoxicity under two-photon excitation (810 nm) and thus was developed as a two-photon photodynamic anticancer agent for cancer therapy.